Knowledge Level Regarding Stunting Among Pregnant Women's - Hamdani, Muhamad Fajar; Rahayu, Yuyun; Noviati, Elis (Inspirasi Foundation, 2024)
Introduction: Stunting is a critical public health issue caused by chronic malnutrition, particularly during the first 1,000 days of life, leading to irreversible impacts on child growth and development. Assessing pregnant women's knowledge about stunting is essential to understanding their role in preventing this condition and improving maternal and child health outcomes. Objective: The objective of this study is to assess the level of knowledge among pregnant women about stunting to identify potential gaps and inform targeted interventions for its prevention. Methods: This study employed a cross-sectional design to assess the knowledge level of pregnant women about stunting. The population consisted of all pregnant women in Mulyajaya, Sumedang Regency, with total sampling used to recruit participants. Data collection took place from March 14 to May 14. The data were analyzed using frequency and percentage distributions with the assistance of SPSS software. Results: The results of this study indicate that the knowledge level of pregnant women about stunting in Mulyajaya Village, Wado Subdistrict, Sumedang Regency is predominantly adequate, with 75% of participants demonstrating a good level of understanding. Conclusions: Strengthening maternal education on stunting is essential for effective prevention efforts. Improving knowledge through targeted educational programs and integrating stunting awareness into antenatal care can enhance maternal and child health outcomes. These efforts can help establish better nutritional practices, reducing the risk of stunting in future generations. Health practitioners play a crucial role in ensuring comprehensive stunting education at the community level.